Retaining Adolescent and Young Adult Participants in Research During a Pandemic: Best Practices From Two Large-Scale Developmental Neuroimaging Studies (NCANDA and ABCD) - Nooner, Kate B.; Chung, Tammy; Feldstein Ewing, Sarah W.; Brumback, Ty; Arwood, Zjanya; Tapert, Susan F.; Brown, Sandra A.; Cottler, Linda (Frontiers in Behavioral Neuroscience, 2021)
The novel coronavirus pandemic that emerged in late 2019 (COVID-19) has created challenges not previously experienced in human research. This paper discusses two large-scale NIH-funded multi-site longitudinal studies of adolescents and young adults-- the National Consortium on Alcohol and Neurodevelopment in Adolescence (NCANDA) and the Adolescent Brain Cognitive Development (ABCD) Study-- and valuable approaches to learn about adaptive processes for conducting developmentally sensitive research with neuroimaging and neurocognitive testing across consortia during a global pandemic. We focus on challenges experienced during the pandemic and modifications that may guide other projects, such as implementing adapted protocols that protect the safety of participants and research staff, and addressing assessment challenges through the use of strategies such as remote and mobile assessments. Given the pandemic's disproportionate impacts on participants typically underrepresented in research, we describe efforts to retain these individuals. The pandemic provides an opportunity to develop adaptive processes that can facilitate future studies’ ability to mobilize effectively and rapidly.